Diffraction imaging of light induced dynamics in xenon-doped helium nanodroplets. (1st November 2022) - Langbehn, B; Ovcharenko, Y; Clark, A; Coreno, M; Cucini, R; Demidovich, A; Drabbels, M; Finetti, P; Di Fraia, M; Giannessi, L; Grazioli, C; Iablonskyi, D; et al.
Abstract: We explore the light induced dynamics in superfluid helium nanodroplets with wide-angle scattering in a pump–probe measurement scheme. The droplets are doped with xenon atoms to facilitate the ignition of a nanoplasma through irradiation with near-infrared laser pulses. After a variable time delay of up to 800 ps, we image the subsequent dynamics using intense extreme ultraviolet pulses from the FERMI free-electron laser. The recorded scattering images exhibit complex intensity fluctuations that are categorized based on their characteristic features. Systematic simulations of wide-angle diffraction patterns are performed, which can qualitatively explain the observed features by employing model shapes with both randomly distributed as well as structured, symmetric distortions. This points to a connection between the dynamics and the positions of the dopants in the droplets. In particular, the structured fluctuations might be governed by an underlying array of quantized vortices in the superfluid droplet as has been observed in previous small-angle diffraction experiments. Our results provide a basis for further investigations of dopant–droplet interactions and associated heating mechanisms.